The Influence of Digital Literacy and Technology Readiness on Innovation Capability of MSMEs in Garut - Fikri Aziz Athoillah; Rahyuniati Setiawan; Anggun Oktavia Herlianti (Entrepreneurship Faculty, Universitas Garut, 2026)
The Indonesian economy relies heavily on contributions from Micro, Small, and Medium Enterprises, yet a substantial number of small businesses operating in Kabupaten Garut remain underutilized in adopting digital technology to stimulate innovative practices. The present work investigates how digital literacy together with technology readiness shape the innovation capability of small businesses in Garut. Adopting a quantitative explanatory design, primary information was gathered via a structured survey administered to 121 owners chosen through purposive selection. Hypothesis testing was conducted with Partial Least Squares Structural Equation Modeling through the SmartPLS 4 software. Empirical evidence shows that both predictors significantly affect innovation capability in a positive direction, although the impact of technology readiness emerged as more pronounced. Approximately 36.7 percent of the variance in innovation capability is captured by the model, accompanied by robust predictive ability. This research enriches scholarly discussions on digital transformation and provides practical guidance for strengthening the foundation of MSME innovation in regional contexts.